Introduction to business statistics : a computer integrated, data analysis approach - Kvanli, Alan H.; Guynes, C. Stephen; Pavur, Robert J. (Cincinnati, Ohio : South-Western College Publishing, 2000)
The book provides a clear understanding of the concepts and applications of statistics while stressing data analysis, graphical interpretation, and decision making.
Includes index.
rua 02/03/15
Loans
Keywords: Statistics - data processing; Commercial statistics; Business statistics